Perkembangan Islam di Kota Medan Pada Masa Sekarang : Study Kasus Perkembangan Islam Kota Medan - Muktaruddin, Muktaruddin; Humairah, Hasyifah; Ismail, Ismail; Rani, Nurraudhoh; Harahap, Sipafadilah (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
Islam first entered Indonesia to be precise in the city of Barus which is located in the Coastal region of Central Tapanuli Regency, North Sumatra. This city is 290 KM from the capital, namely Medan, North Sumatra. If taken by land, it might take as long as 7 hours. However, if you are in Sibolga, this city can be reached in just 2 hours. Long before the emergence of the history of the Wali Songo who spread Islamic teachings in Java, to be precise in the 14th century, Islam was already in Barus. In the 7th century AD, Poly historical literature confirms that the Islamic belief in Indonesia was for the first time in Barus. This can be clarified by the existence of an old tomb in the Mahligai cemetery area, Barus. On the tombstone is written the name of Sheikh Rukunuddin who died in 672 AD or 48 H. This confirms that at that time there was a Muslim community. Keywords: Islamic history of the present day city of Medan, the development of Islam with electronic media in the city of Medan